Site Planning of a Newly Installed LINAC along with a Brachytherapy Unit at CMC, Nepal - Thakur, Subhash; Chawla, Saloni; Koirala, Achyut; Dhakal, Uddhav; Shah, Ramanand (Asian Pacific Journal of Cancer Care, 2022)
The majority of cancer patients will require radiotherapy at some time during their illness, either for curative or palliative purposes, making it an important part of a multidisciplinary cancer treatment approach. External beam radiotherapy and brachytherapy are two methods of administering radiation to the tumor location. Cobalt tele source, Linear accelerator, and Tomotherapy are examples of external beam radiotherapy equipment; similarly, after loading brachytherapy unit is an example of brachytherapy equipment. Because these units generate radiation, a specific site design is required to guarantee that radiation leakage is kept to a minimum. Linear accelerator and Brachytherapy devices are housed in specialized chambers known as “Bunkers.” The engineering of these bunkers is still a difficulty. The layout of the radiation department is designed in such a way that it will smooth the day-to-day operations and maximize the efficiency of the working crew. The general considerations, location, and layout of different rooms built for the LINAC and brachytherapy unit at CMC, Bharatpur, Nepal are discussed in this study.